Practical Classes as a Strategy for Teaching Agricultural Mechanization in the Undergraduate Agronomy Course - Radamés Cabral de França, Pablo (2024)
Practical classes constitute a methodology that allows the application of knowledge acquired in theoretical lessons, enabling the concretization of the discussed topic. The objective of this study was to evaluate a practical class methodology, applied in the course of Machines, Engines, and Agricultural Mechanization at IFPA, Castanhal Campus, regarding the students' performance in evaluations. To develop this, a survey was conducted with the students from the undergraduate Agronomy course at IFPA during the aforementioned discipline. This observational and comparative study analyzed the grades obtained in the discipline of Machine Elements, considering both the practical and theoretical approaches. Based on the results, it was found that the classes obtained higher grades when the topic was addressed and evaluated practically. The practical class connects theoretical knowledge to reality through hands-on experiences.